Early respiratory bacterial detection and anti-staphylococcal antibiotic prophylaxis in young children with cystic fibrosis - Hurley, Matthew; Fogarty, Andrew W.; McKeever, Tricia M.; Goss, Christopher; Rosenfeld, Margaret; Smyth, Alan R. (American Thoracic Society, 2017)
Rationale: Consensus is lacking regarding anti-staphylococcal antibiotic prophylaxis use for young children with cystic fibrosis. Prophylaxis is recommended in the UK, but recommended against in the US. Objectives: To test the hypothesis that anti-staphylococcal antibiotic prophylaxis is associated with a decreased risk of Staphylococcus aureus acquisition, but no increased risk of Pseudomonas aeruginosa acquisition.